A Behavioral Study on Middle-Class Consumers in Adopting M-Commerce in East Java - Mariatul Ulfa Mansyur; Bambang Hariadi; Wuryan Andayani (Jurnal Economia, 2018)
Abstract: A Behavioral Study on Middle-Class Consumers in Adopting M-Commerce in East Java. The objective of this study is to examine factors that influence the behavioral intention of consumers in using and adopting m-commerce. This study combines Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Innovation Diffusion Theory (IDT). The data of this study were collected through a survey and samples were selected by using convenience sampling technique with SEM-PLS requirement as many as ten times the number of paths. The data were analyzed using Partial Least Square (PLS). The results of this study show that perceived usefulness, perceived ease of use, social influence, and personal innovativeness affecs behavioral intention. Furthermore, behavioral intention affects actual user, i.e. consumers, to use and adopt m-commerce information technology. This study implies that vendors of m-commerce information technology and management should pay more attention to and reconsider perceived usefulness, perceived ease of use, social influence, personal innovativeness, behavioral intention, and consumers as actual users, when they make decision regarding adoption and appliance of m-commerce.Keywords: m-commerce information technology adoption, consumer behavior, Technology Acceptance Model, Theory of Planned Behavior, Innovation Diffusion TheoryAbstrak: Studi Keperilakuan Konsumen Kelas Menengah dalam Pengadopsian M-Commerce di Jawa Timur. Studi ini bertujuan untuk menguji faktor-faktor yang memengaruhi minat perilaku konsumen dalam menggunakan maupun mengadopsi m-commerce. Studi ini merupakan penggabungan model Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), dan Innovation Diffusion Theory (IDT). Studi ini menggunakan metode survey, sampel dipilih dengan menggunakan teknik convenience sampling, dan teknik analisis yang digunakan adalah SEM-PLS. Studi ini menemukan bahwa konstruk persepsi kegunaan, persepsi kemudahan penggunaan, pengaruh sosial dan keinovatifan pribadi berpengaruh terhadap minat perilaku. Selanjutnya, studi ini juga menemukan bahwa minat perilaku berpengaruh terhadap pengguna yang sesungguhnya, yaitu konsumen, terkait dengan penggunaan maupun adopsi m-commerce. Implikasi studi ini adalah vendor layanan teknologi informasi m-commerce dan manajemen harus memperhatikan dan mempertimbangkan lagi persepsi kegunaan, persepsi kemudahan, pengaruh sosial, keinovatifan pribadi, minat perilaku dan konsumen sebagai pengguna sesungguhnya dalam mengambil keputusan terkait dengan pengenalan dan adopsi m-commerce.Kata kunci: Adopsi Teknologi Informasi M-commerce, Perilaku Konsumen, Technology Acceptance Model, Theory of Planned Behavior, Innovation Diffusion Theory